An extended two-phase model for Mullins effect in swollen rubber - Chai, A.B.; Andriyana, A.; Ch'ng, S.Y.; Verron, E.; Johan, M.R. (Maney Publishing, 2014)
It is well-known that dry rubber exhibits Mullins effect under cyclic loading condition. For swollen rubber, this response is found to strongly depend on the degree of swelling. In the present work, the modelling of the Mullins effect in swollen rubber under cyclic compressive loading is addressed. Different degrees of swelling are obtained by immersing initially dry rubber in biodiesel. The two-phase model of Mullins and Tobin [L. Mullins and N. R. Tobin: `Theoretical model for the elastic behaviour of filler reinforced vulcanized rubbers', Rubber Chem. Technol. 1957, 30, 551-571] and Qi and Boyce [H. Qi and M. C. Boyce: `Constitutive model for stretch degrees (c)-induced softening of the stress-stretch behavior of elastomeric materials', J. Mech. Phys. Solids, 2004, 52, (10), 2187-2205] is considered and extended in order to capture the effect of swelling on the Mullins effect. Results show that the proposed model agree well with the experimental findings.